2013
DOI: 10.1111/liv.12201
|View full text |Cite
|
Sign up to set email alerts
|

The inpatient economic and mortality impact of hepatocellular carcinoma from 2005 to 2009: analysis of the US nationwide inpatient sample

Abstract: There is an increase in the number of inpatient cases of HCC. Although inpatient mortality is decreasing and the LoS is stable, the inpatient charges associated with HCC continue to increase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 12 publications
0
31
0
Order By: Relevance
“…Despite these modest effects, sorafenib is currently the most effective chemotherapeutic option for metastatic HCC. Given the limited treatment options and the significant economic impact of end stage HCC, there is a great need for new and combination therapies (9). …”
Section: Introductionmentioning
confidence: 99%
“…Despite these modest effects, sorafenib is currently the most effective chemotherapeutic option for metastatic HCC. Given the limited treatment options and the significant economic impact of end stage HCC, there is a great need for new and combination therapies (9). …”
Section: Introductionmentioning
confidence: 99%
“…Chronic hepatitis C (CHC) is the most common cause of cirrhosis and its complications (hepatocellular carcinoma) in the United States and the Western world . CHC has been associated with increased mortality and resource utilization as well as impairment of patients' well‐being .…”
mentioning
confidence: 99%
“…C hronic hepatitis C (CHC) is the most common cause of cirrhosis and its complications (hepatocellular carcinoma) in the United States and the Western world. [1][2][3][4][5][6][7][8][9] CHC has been associated with increased mortality and resource utilization as well as impairment of patients' well-being. 4 Although hepatitis C virus (HCV), by itself, can negatively affect patient-reported outcomes (PROs), presence of cirrhosis, especially in its advanced form, can further deteriorate this impairment.…”
mentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) currently, affects 1.5% of the world population and reach approximately 15% of patients on the waiting list for liver transplantation (1,11,21) . Mishra et al (28) has demonstrated that the costs of treating patients with HCC in 2009 were around US$ 31 thousand, with total treatment costs of ap proximately US$ 2 billion in the USA.…”
Section: Introductionmentioning
confidence: 99%
“…Higher MELD score increases the overall cost on the waiting list for liver transplantation: a micro-costing analysis based study Brazil, the annual cost of heath care of each patient with advanced liver disease can reach more than 20 thousand dollars (1,2,11,27,28,38,44,49) . Some correlated disease has strong linkage with high costs procedures and hospitalizations.…”
Section: Introductionmentioning
confidence: 99%